Pupuk Picuras (Pemanfaatan Limbah Air Cucian Beras Dan Kulit Pisang Kepok Menjadi Pupuk Organik Cair Yang Ramah Lingkungan) (Fakultas Teknik, Universitas Brawijaya, 2024)
One alternative fertilizer that can be used by farmers so that it does not have a negative impact on the environment and health is Liquid Organic Fertilizer (POC). Some organic materials that can be used to make Liquid Organic Fertilizer (POC) are rice washing water and banana peels which contain nutrients that are good for plant growth. The purpose of this activity is to find out the benefits of banana peels as Liquid Organic Fertilizer (POC). The method used in this activity is a qualitative method and the data collection techniques used are observation and interviews. Based on the survey results, household waste processing in Ngadilangkung Village has not been fully processed by each household, such as rice washing water waste which is only thrown away directly and not used as fertilizer, but for some people the rice washing water is poured on the plants. All locations producing banana kepok waste, such as fried banana sellers, banana molen, and bird feed have also not processed. This shows that there is still a lack of public knowledge regarding the utilization and processing of household waste in Ngadilangkung Village. In this community service activity, socialization was carried out on the manufacture of liquid organic fertilizer by utilizing rice washing water waste and banana peels. The results of the activities show an increase in community awareness and ability in managing waste and reducing dependence on chemical fertilizers.